The Palma Echo Platform: Rationale and Design of an Echocardiography Core Lab - López, Luis; Rossello, Xavier; Romaguera, Dora; Alonso-Gómez, Ángel M.; Toledo, Estefanía; Fortuny, Elena; Noris, Marta; Mas-Lladó, Caterina; Fiol, Miquel; Ramallal, Raul; Tojal-Sierra, Lucas; Alonso, Alvaro; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The metabolic syndrome (MetS) is associated with increased cardiovascular morbidity and mortality. Characterization of cardiac structural and functional abnormalities due to the MetS can help recognize individuals who would benefit the most from preventive interventions. Transthoracic echocardiography (TTE) provides an opportunity to identify those abnormalities in a reproducible and cost-efficient manner. In research settings, implementation of protocols for the acquisition and analysis of TTE images are key to ensure validity and reproducibility, thus facilitating answering relevant questions about the association of the MetS with cardiac alterations. Methods and Results: The Palma Echo Platform (PEP) is a coordinated network that is built up to evaluate the underlying structural and functional cardiac substrate of participants with MetS. Repeated TTE will be used to evaluate 5-year changes in the cardiac structure and function in a group of 565 individuals participating in a randomized trial of a lifestyle intervention for the primary prevention of cardiovascular disease. The echocardiographic studies will be performed at three study sites, and will be centrally evaluated at the PEP core laboratory. Planned analyses will involve evaluating the effect of the lifestyle intervention on cardiac structure and function, and the association of the MetS and its components with changes in cardiac structure and function. Particular emphasis will be placed on evaluating parameters of left atrial structure and function, which have received more limited attention in past investigations. This PEP will be available for future studies addressing comparable questions. Conclusions: In this article we describe the protocol of a central echocardiography laboratory for the study of functional and structural alterations of the MetS.